Behavior of RCS Connections with Void Web Under Cyclic Load Reversals - Yudi Herdiansah; Bambang Budiono; Herlien Dwiarti Soemari; Indra Djati Sidi (Journal of Engineering and Technological Sciences, 2020)
In this study, the inelastic cyclic behavior of hybrid connections consisting of reinforced concrete column and steel beams (RCS) was investigated. The experimental results from the lateral load testing of four interior RCS subassembly connections are presented. The first specimen was designed based on the ASCE Guidelines 1994, with connection details based on the study of Liang and Parra-Montesinos (2004), while another specimen was a proposed joint detail. The joint detail was developed to overcome the main problems with RCS frame systems, which is constructability. The behavior of the beam-column joints was evaluated in terms of strength capacity, stiffness degradation, energy dissipation, and joint shear distortion. Comparing all specimens based on the load-displacement hysteresis curves indicated that the specimen with the combination of ABP and EBP had relatively better performance in terms of strength, stiffness, and energy dissipation. ABP and EBF in the joint with a void web were able to withstand joint shear deformation exceeding 0.01 rad, with only low to medium level of damage. EBF was proven to be very effective in providing confinement and reducing the damage level in the joint panel. The existence of a void web did not affect the reduction of joint shear strength.